Development of a peptide-based delivery platform for targeting malignant brain tumors. (September 2020) - Rahn, Jennifer J.; Lun, Xueqing; Jorch, Selina K.; Hao, Xiaoguang; Venugopal, Chitra; Vora, Parvez; Ahn, Bo Young; Babes, Liane; Alshehri, Mana M.; Cairncross, J. Gregory; Singh, Sheila K.; Kubes, Paul; et al.
Abstract: Despite extensive molecular characterization, human glioblastoma remains a fatal disease with survival rates measured in months. Little improvement is seen with standard surgery, radiotherapy and chemotherapy. Clinical progress is hampered by the inability to detect and target glioblastoma disease reservoirs based on a diffuse invasive pattern and the presence of molecular and phenotypic heterogeneity. The goal of this study was to target the invasive and stem-like glioblastoma cells that evade first-line treatments using agents capable of delivering imaging enhancers or biotherapeutic cargo. To accomplish this, a combinatorial phage display library was biopanned against glioblastoma cell model systems that accurately recapitulate the intra- and inter-tumor heterogeneity and infiltrative nature of the disease. Candidate peptides were screened for specificity and ability to target glioblastoma cells in vivo . Cargo-conjugated peptides delivered contrast-enhancing agents to highly infiltrative tumor populations in intracranial xenograft models without the obvious need for blood brain barrier disruption. Simultaneous use of five independent targeting peptides provided greater coverage of this complex tumor and selected peptides have the capacity to deliver a therapeutic cargo (oncolytic virus VSVΔM51) to the tumor cells in vivo. Herein, we have identified a series of peptides with utility as an innovative platform to assist in targeting glioblastoma for the purpose of diagnostic or prognostic imaging, image-guided surgery, and/or improved delivery of therapeutic agents to glioblastoma cells implicated in disease relapse.